2011
DOI: 10.1007/s00259-011-1738-8
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-fluorodeoxyglucose uptake in positron emission tomography/computed tomography in predicting survival in multiple myeloma

Abstract: PET/CT allows identification of high-risk myeloma patients, and extramedullary lesions with the highest SUV(max) independently predict inferior OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 22 publications
5
43
0
1
Order By: Relevance
“…However, the new imaging parameter MTV, derived from SUVmax, showed prognostic significance, likely because MTV takes into account the metabolic active volume of all MM lesions, which can vary in size and uptake and be widespread throughout the body. A recent study reported that patients affected by MM at different stages with 18 F-FDG uptake-positive extramedullary lesions showed a shorter survival than patients without 18 F-FDG-positive lesions; the study also found that the SUVmax of the extramedullary lesion with the highest metabolic uptake was significantly associated with overall survival (35). In our study, we enrolled MM patients who were in the same stage.…”
Section: Discussionmentioning
confidence: 84%
“…However, the new imaging parameter MTV, derived from SUVmax, showed prognostic significance, likely because MTV takes into account the metabolic active volume of all MM lesions, which can vary in size and uptake and be widespread throughout the body. A recent study reported that patients affected by MM at different stages with 18 F-FDG uptake-positive extramedullary lesions showed a shorter survival than patients without 18 F-FDG-positive lesions; the study also found that the SUVmax of the extramedullary lesion with the highest metabolic uptake was significantly associated with overall survival (35). In our study, we enrolled MM patients who were in the same stage.…”
Section: Discussionmentioning
confidence: 84%
“…On the contrary, the PET parameter SUV has rarely been connected to baseline clinical characteristics. Although there were several studies suggesting that SUV at diagnosis has a prognostic impact, there was no unifying definition of SUV used in these studies; the mean value of SUV [31] or SUV max [33] was arbitrarily cited. In our study, we evaluated the correlation between SUV max at diagnosis and baseline clinical characteristics and observed no significant relationship.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, an X-ray is less sensitive than other imaging modalities at detecting both medullary and extramedullary lesions as well as at identifying bone marrow (BM) involvement [20,21,22,23,24]; therefore, it serves as a less accurate modality for staging MM [25,26,27,28,29]. In addition to staging at the time of initial diagnosis, newer imaging techniques allow for improved understanding of the prognosis of a disease [17,30,31,32,33]. In brief, radiological imaging goes beyond simply detecting ‘morphological' findings but reflects disease aggressiveness and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT has the highest detection rates for extramedullary disease (EMD; ref. 34) compared with other imaging techniques, which is critical, since EMD has been found to confer a poor prognosis (24,27,35,36). Only one study examined the prognostic value of lesions found on CT, and showed no correlation between the number of lesions and prognosis (30).…”
Section: Imaging For Surveillance and Prognosticationmentioning
confidence: 99%
“…The most significant advantage in the use of PET/CT is through detection of disease activity as it can distinguish between active and inactive disease (22). PET results correlate with clinical and hematologic parameters in patients with multiple myeloma (23), and can predict survival (24). Limitations of PET imaging include poor specificity to small lytic lesions less than 0.5 cm in size and false-positive results.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%